PENGENDALIAN ULAT GRAYAK (Spodoptera litura F.) PADA TANAMAN UBI JALAR (HIPERE) MENGGUNAKAN EKSTRAK DIWOKA (Piper miniatum Bl.) SEBAGAI SALAH SATU TANAMAN ENDEMIK PEGUNUNGAN TENGAH PAPUA, INDONESIA - Inrianti Inrianti; Sepling Paling; Les Murib (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
One type of pest that has begun to invade several types of plants in Jayawijaya Regency including hypere plants is the Fall Armyworm pest (Spodoptera litura F.). Armyworms are not the primary (main) pest on hypere plants. However, it is a secondary pest because it can attack several types of plants. However, the occurrence of a population explosion will cause higher damage to the attacked plants. The aim of this study was to determine the effect of various concentrations of diwoka leaf extract (Piper miniatum Bl.) on the mortality of Grayak caterpillar (Spodoptera litura F.) on sweet potato (Hipere) and the extract concentration which was more effective in controlling Grayak caterpillar pests (Spodoptera litura F.) in sweet potato plant (Hipere). The treatments tried were: 1. Control (sterile water application), 2. Diwoka leaf application 40%, 50%, 60%, 70%, 80%, 90% through food (stomach poison). The experiment was arranged in a completely randomized design with four replications each using 250 instar larvae of Spodoptera litura.F. Observations showed that there was an effect of each concentration tested on Spodoptera litura.F through food (stomach poison). Of the six treatments of diwoka leaf extract which was applied during the preliminary test on the fifth instar with a concentration of 70% showed a significant effect on the mortality rate of Spodoptera litura.F. After conducting a preliminary test and then carrying out further tests on the second instar larvae where in that instar the attack rate was very high, so the concentration used was 40%-90%. All concentrations showed a significant effect on second instar larvae, at a concentration of 40% the mortality rate was 12.50%, and the highest concentration was 90% with a mortality rate of 80%.